Pre-conversion soil organic carbon level did not affect accumulation rate following conversion from arable land to semi-natural grassland - Johannes L. Jensen; Jørgen Eriksen; Bent T. Christensen (Geoderma, 2024)
Converting arable land to permanent grassland may favor SOC sequestration and thus climate change mitigation. We studied a field experiment on coarse sand soil that during 1894–1997 was under arable rotation with various nutrient treatments (unfertilized, mineral fertilizer, animal manure), leading to topsoils with different SOC contents. In 1998, the treatments stopped, and a semi-natural grassland has been established with topsoil sampled seven times during the following 26 years. Introduction of grassland increased topsoil SOC content linearly at a rate of 0.30 ± 0.01 Mg C ha−1 yr−1, unaffected by pre-conversion SOC level and with no sign of steady state. By mitigating the loss of SOC associated with continued arable cropping, the overall benefit of this land conversion becomes 0.39 Mg C ha−1 yr−1 during the period 1998 to 2023.